(untitled) (Fiep Bulletin - online, 2014)
Aging in all body functions decline, the loss of autonomy becomes a major obstacle especially in performing daily activities, so the present study aimed to verify the influence of physical activity in daily life activities of elderly group participants fitness for a particular institution of Porto Alegre. The study of quantitative, field, descriptive was conducted with 30 patients of both sexes aged over 60 years, all of whom participated in the group exercise twice a week. For data collection, we used the IPAQ long form adapted for seniors and testing protocol GDLAM (Latin American Development Group to Maturity) for the evaluation of functional autonomy, as measured by time in seconds. This study serves as the basis for a better understanding of the reality of the elderly who attend group fitness in relation to functional independence, where the results show that in spite of practicing physical activity, the elderly did not have a good performance in the tests, it is due to the fact a good portion do not practice regular exercise, ie, the frequency of physical activity are less than three times per week, thus confirming the results of the testing protocol GDLAM which was considered mostly with poor results.